Placement of an internal–external biliary drain through a bilio‐enteric fistula in a neonate to re‐establish antegrade bile flow after liver transplantation. (19th August 2014) - Parra, Dimitri A.; Fecteau, Annie; Connolly, Bairbre L.
Abstract Three‐month‐old baby girl with history of post‐liver transplant hepatic artery dissection treated with ligation after take down of the biliary anastomosis and placement of a surgical external common bile duct drain. There was persistent malfunction of this drain. A bilio‐enteric fistula was noted during the later placement of an image guided percutaneous external drain. Subsequently, an internal–external biliary drain was successfully placed through this fistula. An excellent clinical and functional result was achieved.